Restoring nature the evolution of Channel Islands National Park - Dilsaver, Lary M.; Babalis, Timothy (America's public lands., 2023)
Restoring Nature examines how the National Park Service has sought to reestablish native species and eradicate the exotic flora and fauna from Channel Islands National Park, and explores why the damage happened in the first place.